Treatment of Medial Tibial Stress Syndrome according to the Fascial Distortion Model: A Prospective Case Control Study - Christoph Schulze; Susanne Finze; Rainer Bader; Andreas Lison (The Scientific World Journal)
Medial tibial stress syndrome (MTSS) is a common problem among athletes and soldiers. There is no proven theory that could explain the pathophysiology of shin splints. The therapies described so far are time-consuming and involve a high risk of relapse. The method according to the fascial distortion model (FDM) addresses local changes in the area of the lower leg fascia. It is suited to reduce pain and functional impairments associated with this symptom complex by applying targeted manual techniques. 32 patients (male: 30; female: 2) participated in this study. Visual analogue scale (VAS) was used for the quantification of pain. Scores were also given to rate the maximum painless exercise tolerance of the patients. Subsequently treatment of the crural fascia was performed. Patients retested ability of running and jumping. Therapy was continued until full exercise tolerance or painlessness was reached. A significant reduction of the VAS pain score from 5.2 to 1.1 could be achieved (P<0.001). The impairment of exercise tolerance could be reduced from 7 to 2 points (P<0.001). The duration of treatment was 6.3 (SD: 4.3) days on average. The FDM therapy is a potential effective method for acute treatment of MTSS.